A new technique for producing high-velocity liquid-like jet - Y.A, Mazin; N. K, Riyah (Anbar Journal of Engineering Sciences, 2008)
A new technique is presented by which lateral outflows of material , from an oblique impact collision between wax projectile and a rigid surface , are collected to form a high speed single jet. This jet has been shown to be capable of producing cavities in semi-infinite target of wax in a manner similar to that produced in a hypervelocity impact situation. The produced jet capability of penetration is found to be maximum at higher velocities of impact , lower values of standoff and with projectiles having angle of obliquity in the range (â=20-25o). A preliminary theoretical model is also presented in an attempt to describe the process of jet creation and jet characteristics. The present technique is proved to be promising in simulating penetration of semi-infinite targets by the impact of high speed jet .